Little Pharmacist "Apocil" Training for Elementary School Students in Sokong Village, Tanjung, North Lombok - Ayu Pratama Kinanti; Titi Pudji Rahayu; H Herniyatun (Prosiding University Research Colloquium, 2022)
Various health problems related to the use of drugs are still commonly encountered in the community. The cause of these problems is the lack of public awareness of the importance of good drug use and management. Self-medication or what is often called "swamedikasi" is one of the community's efforts to maintain their own health, but selfmedication can be the root of problems related to drug use (Drug Related Problem). Little Pharmacist or Small Pharmacist commonly abbreviated as Apocil is an idea to increase the role of the pharmacist profession more clearly from an early age. It is hoped that the presence of this little pharmacist in the future can increase students' awareness regarding drugs and introduce the pharmacist profession to students and the public. This community service activity was carried out on Thursday, September 2, 2021 at 12.30- 15.30 WITA which was located at the 032 Group KKN-Mas Command Post to be precise in Prawira Hamlet, Sokong Village, Tanjung District, North Lombok Regency. The targets in this activity are elementary school-level children in Sokong Village, Tanjung District, North Lombok Regency from grades I-VI, totaling 25 students. The purpose of this community service activity is to introduce the pharmacist profession as a health worker and source of drug information and provide education to children from an early age on how to get, use, store and dispose of drugs properly. This community service activity was carried out using the pre-experimental design method, type one group pretest-posttest. Service activities are carried out by providing education and socialization about the pharmacist profession, introduction of types of drugs and how to use them. The training was carried out using the presentation method using Power Point as a media, with interesting pictures so that participants could know clearly and not feel bored. All participants seemed enthusiastic in answering the questions posed by the service team. This can be seen from almost all students raising their hands to try to answer the questions posed by the service team. Based on the results of the evaluation of community service activities, it showed that most students (80%) were able to explain what a pharmacist is, where he works, what drugs are, types of drug dosage forms, classification of drugs based on their logos, how to get good drugs and the use of drugs that are appropriate.